The Influence of Competence, Independence, Interest, and Discipline on The Readiness of Working in Vocational School Students in Lombok Barat District - Muhammad Ridho Prihatin; Fatwa Tentama; Budi Santosa; Aji Apri Setiawan (Universitas Ahmad Dahlan, 2020)
This study aims to determine the effect of competence, independence, interest and discipline individually or jointly on the work readiness of vocational school students in West Lombok District. The population of this study was the students of Agro Business Competencies in Agricultural Product Processing Vocational High School in West Lombok Regency, with a sample of 67 students. Data collection uses a Likert scale questionnaire and five alternative answers. Data of all variables were analyzed with descriptive statistics with an average value of students' work readiness of 82.5%. The effect of each independent variable on the dependent variable was analyzed by partial correlation statistics and multiple regression analysis. The interpretation of the results of data analysis uses a significant level of 5% or 0.05. The results showed a very significant influence between competence, independence, interest and discipline on the work readiness of vocational students in West Lombok district with a significance value of 0,000 and a coefficient of determination of 0.462 or 46.2% meaning together the contribution of all the independent variable to the dependent variable is the remaining 46.2% of 53.8% by variables and other factors outside this study that were not explained by the researcher.Vocational School, Competence, Independence, Interest, Discipline, Work Readiness.